THE WELFARE EVALUATION OF QURBAN CATTLE BASED ON MEAT QUALITY AT THREE SLAUGHTERHOUSES IN PALANGKA RAYA CITY - Siti Ma'rifah; Ferdian Rafli Aditya; Satrio Wibowo; Heri Sujoko; Asri Pudjirahaju (Fakultas Kedokteran Hewan Universitas Udayana, 2026)
This study aimed to evaluate the welfare of sacrificial (qurban) cattle based on meat quality at three slaughter locations in Palangka Raya City. Observed parameters included meat color, texture, odor, pH, moisture content, shelf life, and cooking loss, along with animal welfare assessed through the Five Freedoms framework. The research employed direct observation and laboratory analysis of meat samples from each site. Results indicated that animal welfare was generally practiced to a fair degree; however, basic needs such as feeding and watering prior to slaughter were often neglected. The meat quality from two locations was found to be superior compared to another, as indicated by lower pH values and longer shelf life. Correlation analysis revealed a significant relationship between moisture content and weight loss (r = 0.61; p < 0.05). These findings highlight that proper implementation of animal welfare practices positively influences the quality of qurban beef. Therefore, improvements in pre- and post-slaughter management are necessary to ensure the future quality and safety of qurban meat products.